An experimental and numerical investigation on the process efficiency of the focused TIG welding of Inconel 718 thick plates - Salerno, Gervasio; Bennett, Chris; Sun, Wei; Becker, Adib A. (SAGE, 2018)
A combined experimental and numerical approach was adopted to investigate the focused tungsten inert gas (TIG) welding process by producing bead-on-plate welds in Inconel 718 plates. Experimental investigations were carried out by means of thermocouple measurements and optical macrographs of the weld cross-section. Three dimensional finite element (FE) simulations were conducted using the commercial specialized FE software Sysweld in order to predict the thermal field induced by the process in the plates. The work presents an approach to investigate the process efficiency and calibrate the heat source model in order to produce a full thermal characterization the plasmatron welding apparatus.